Measuring Straight Time in Elite Short Track Speed Skating Relays. (2016) - Hext, Andrew; Heller, Ben; Kelley, John; Goodwill, Simon
Abstract: In short track speed skating, the relay exchange provides an additional strategic component to races by allowing a team to change the skater involved in the pack race. It is thought that during this period of the race, time can be gained or lost due to the execution of the relay exchange. However, the only temporal measurement reported in short track speed skating is lap time, of which the relay exchange accounts for less than 30%. As such, a more appropriate measurement of relay exchange performance might be the time taken to complete the straight where the relay exchange was executed. The aim of this study, therefore, was to validate a method for measuring straight time during elite short track speed skating relays. The proposed method used a single HD camcorder to create virtual timing gates at the start and end of both straights. To validate the method, straight times measured using the single HD camcorder were compared to synchronised cameras located perpendicular to the virtual timing gates. The root mean square error for both near and far straight times was less than the temporal resolution of the camera. In addition, Bland-Altman plots showed that the single HD camcorder method was invariant to race speed. Collectively, these findings suggest that a single HD camcorder does provide a valid method for measuring straight times during elite short track speed skating relays.